KUASA ALGORITMIK DALAM MASYARAKAT DIGITAL (INTERPRETASI PANDANGAN FOUCAULT ATAS TEKNOLOGI) - Wamil Nur; Suratman Kayano (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2020)
Nowadays, study about digital society had been excessively done. This study could not be released by quickly developing innovation of technology in many flanks human life. Innovations of technology showed optimism and pessimism in various realm. The development of speed spaces expressed phenomenon moreover argumentation which sanctioning human ability to manage the technology that they were created. Therefore, this study tries to become disentangled technology development by using Michael Foucault’s conceptual framework for explaining algorithmic power subjects and algorithmic governmentality in digital society. This study used qualitative descriptive approach with document research method along with content analysis method from primary resource and secondary resource till this study can be able to answer questions which was the basis why this study shall be doing. The results of this research shows there are power relations among actors like country and global capitalism within constructing freedom fantasies and democracy on digital society. For creating submissive society, every power actors used development of technology to predict and control critical awareness of society pass through algorithmic subjects and governmentality. As expressed by Michael Foucault, technology had been created for power to dominate digital society and created normality in human life. This study was offering practical steps to critical people to formulate algorithmic governmentality in a way to build their own technology to transform specific goals achievement like happiness, purity and wisdom as well as perfection and eternity.